Elucidating the binding mechanism of Caralluma tuberculata metabolites with type 2 diabetes targets through molecular docking and dynamics simulations - Amir Ali; Zia-ur-Rehman Mashwani; Ashfaq Ahmad; Juan Pedro Luna-Arias; Gabriela Medina-Pérez; Ajaz Ahmad (PLoS ONE, 2026)
Introduction Caralluma tuberculata , a medicinal plant from the Apocynaceae family, has been traditionally used to manage diabetes due to its rich secondary metabolite content. Methodology This study employed LC/ESI-MS/MS analysis to identify bioactive compounds in C. tuberculata , followed by in silico screening for their inhibitory effects on key carbohydrate-digesting enzymes—alpha-amylase, sucrase, and alpha-glucosidase associated with type 2 diabetes. A total of 57 compounds were evaluated through molecular docking, toxicity prediction, drug-likeness analysis, and molecular dynamics (MD) simulations. Results Among these, luteolin exhibited the highest binding affinities with amylase (−9.725 kcal/mol), sucrase (−8.19 kcal/mol), and alpha-glucosidase (−7.842 kcal/mol), while also demonstrating no predicted toxicity. MD simulations over 60 ns revealed stable root mean square deviation (RMSD) profiles for all protein-ligand complexes, confirming system stability. Free binding energy calculations (MM-PBSA and MM-GBSA) further suggested that luteolin had stronger, more stable interactions with amylase and sucrase compared to glucosidase. Conclusion This study provides a comprehensive computational evaluation of luteolin derived from Caralluma tuberculata , offering detailed insights into its enzyme-specific interactions with key carbohydrate hydrolyzing enzymes relevant to type 2 diabetes. Although the results are promising, experimental and clinical validation is essential to confirm luteolin’s therapeutic efficacy for managing type 2 diabetes.